A Fast Fault Location Based on a New Proposed Modern Metaheuristic Optimization Algorithm - Mohammad Parpaei; Hossein Askarian-Abyaneh; Farzad Razavi (AUT Journal of Electrical Engineering)
Double-circuit power systems are one of the main types of modern transmission lines due to their reliability. Fault location in these transmission lines has always been a potential problem due to the mutual coupling between lines. Accordingly, this paper presents a novel objective function for the fault location using synchronous post-fault measurements of currents and voltages captured by distance protective relays. Moreover, a fast and accurate modern metaheuristic optimization algorithm for this cost function is proposed, which are key parameters to estimate the fault location methods based on optimization algorithms. In this regard, first, the input data (current and voltage signals) were refined using some auxiliary functions such as Fast Fourier transformation (FFT), Decaying Dc Elimination (DDE), and frequency tracking algorithm to accurately extract the fundamental component of the voltage and current signals. Afterwards, the proposed fault location based on the proposed metaheuristic optimization algorithm estimates the fault location using these input signals. The main advantage of the presented algorithm is the parallel estimation processing to improve the convergence speed and the accuracy of the objective function of the fault location, and was applied to various fault types and various operating conditions to validate the performance of the proposed approach. In addition, the performance of the proposed method was compared with different fault location methods. The simulation was implemented in the PSCAD and MATLAB® software. The simulation results show that the novel proposed approach outperforms other fault locations in estimating the fault location.